Throw down your heart [videorecording (DVD)] - Paladino, Sascha; Paladino, Sascha; Fleck, Béla, 1958- (Docurama Films : Distributed by New Video Group, Inc., 2009)
Multiple Grammy-winner Béla Fleck travels to Uganda, Tanzania, the Gambia, and Mali searching for the roots of the banjo. Part road movie, part historical document, this fascinating film demonstrates the power of music and musicians to reach across cultural boundaries and the limitations of language to create an instant and abiding connection. Whether plaintive or pulsating, the infectious music in Throw Down Your Heart transports viewers into the heart of Fleck's personal journey.